Studi Empiris tentang Hubungan antara Kepuasan Kerja, Efikasi Diri, dan Kinerja Pegawai di Kementerian Agama Banda Aceh - Masyithah, Syarifah Mauli; Jumeil, T Muhammad; Yunidar, Syafira; Nurrahmad, Nurrahmad (Center for Research and Community Service (LPPM) University of Abulyatama, 2025)
The objective of this study is to determine the influence of job satisfaction and self-efficacy, both partially and simultaneously, on the performance of employees at the Ministry of Religious Affairs Office in Banda Aceh City. The sample size for this study consists of 98 respondents. The research method employed is quantitative. Data were collected through questionnaires and analyzed using a multiple linear regression model. Hypothesis testing was conducted using multiple linear regression analysis, F-test, and t-test to determine the partial and simultaneous effects of the independent variables on the dependent variable. The results of the study indicate that job satisfaction has a significant partial effect on employee performance at the Ministry of Religious Affairs Office in Banda Aceh City. Self-efficacy, on the other hand, does not have a significant partial effect on employee performance at the same office. However, job satisfaction and self-efficacy together have a very significant simultaneous effect on employee performance at the Ministry of Religious Affairs Office in Banda Aceh City. The conclusion based on the simultaneous test shows that job satisfaction and self-efficacy together have a very significant effect on employee performance at the Ministry of Religious Affairs Office in Banda Aceh City.